The New TLC Method for Separation and Determination of Multicomponent Mixtures of Plant Extracts - Elżbieta Matysik; Anna Woźniak; Roman Paduch; Robert Rejdak; Beata Polak; Helena Donica (Journal of Analytical Methods in Chemistry)
The new mode of two-dimensional gradient thin layer chromatography (MGD-2D TLC) has been presented. Short distance development of sample in the first dimension leads to formation of the preconcentrated narrow zones. They are consecutively separated in the second dimension with the mobile phase gradient in several steps of development until the eluent reaches the further end of the chromatographic plate. The use of the above-mentioned technique allows isolating and then identifying the compounds of various polarity from the multicomponent mixture. The practical application of two-dimensional gradient thin layer chromatography has been performed for isolation of the two plant (Juniperus and Thymus) oils components as the examples of test mixtures. The experiments have been carried out with the use of silica gel plates as well as a normal phase condition. The results of solute separation with isocratic one-dimensional thin layer chromatography system have been compared with those of two-dimensional gradient system. It has been observed that application of the latter mode leads to almost triplicated number of zones in comparison with the former one. It is purposeful to apply the proposed mode to control the purity of the dominant component or components of the mixture.